Can Project Managers' emotional intelligence contribute to the success of construction projects? - Hanafi, Abdul Ghafur (2019)
Today, the challenges faced by a construction project manager are to improve the level of efficiency and overall productivity levels while at the same time maintaining harmonious relationships with stakeholders. They need to be able to communicate and interact at an all level and know how to use tools and methods to improve outcomes. Although Emotional Intelligence is an individual capability concerning a project team, it can provide a level of motivation and energy for the entire project team to detect and avoid any sign of project failure. To be aligned appropriately, a good project manager should be able to evaluate and track potential risks and make clear plans and manage the project. This article examines Emotional Intelligence as one of the drivers for the project manager's achievement and shows how to combine Emotional Intelligence and effective project management. If Emotional Intelligence focuses mainly on the level of communication within management staff, the ultimate goal of project management is to avoid defects during and after project, efficient time management, overall cost-controlled, and comprehensive project planning structured thoroughly into achieving a successful project. The question is, in the end, "Can project managers' Emotional intelligence contributes to the success of construction projects?" By combining several critical aspects of Emotional Intelligence, this paper proposes a more comprehensive approach to how construction project management is managed in the future.